2018
DOI: 10.1142/s0219455418501535
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform Heat Effects on Buckling of Laminated Composite Beam: Experimental Investigations

Abstract: The influence of nonuniform heating on the critical buckling temperature of laminated glass-epoxy composite beam has been investigated experimentally with the help of a novel experimental setup. The beam is numerically investigated using nonlinear finite element analysis. An initial geometric imperfection is introduced to the modeled geometry in numerical technique to have an experimental–numerical comparison of temperature-deflection plot. The results indicate that the critical buckling temperature of a unifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The location of heat input and the temperature distribution of the beam will influence the critical buckling temperature of a composite beam. George et al [21] experimented with the thermal buckling behavior of laminated glass fiber reinforced epoxy-based composite beam under non-uniform heat input to estimate the critical buckling temperature of the studied beam. Muc et al [22] investigated the postbuckling characteristics and stability loss of multilayered composite beams.…”
Section: Introductionmentioning
confidence: 99%
“…The location of heat input and the temperature distribution of the beam will influence the critical buckling temperature of a composite beam. George et al [21] experimented with the thermal buckling behavior of laminated glass fiber reinforced epoxy-based composite beam under non-uniform heat input to estimate the critical buckling temperature of the studied beam. Muc et al [22] investigated the postbuckling characteristics and stability loss of multilayered composite beams.…”
Section: Introductionmentioning
confidence: 99%
“…11 Similarly, experimental investigations were also made to investigate the buckling behavior of a laminated composite beam under different types of temperature distributions. 12…”
Section: Introductionmentioning
confidence: 99%
“…11 Similarly, experimental investigations were also made to investigate the buckling behavior of a laminated composite beam under different types of temperature distributions. 12 Studies on the vibro-acoustic response of heated structures under a steady-state mechanical excitation are limited compared to studies on heated structures' static, buckling, and dynamic behavior. A comprehensive analysis of the buckling and dynamic (vibration and acoustic) behavior of a uniformly heated isotropic plate and their numerical study revealed that elevated temperature significantly influences the resonant vibration and sound response amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…George et al, 4 George, and Jeyaraj 5 have conducted theoretical and experimental research on the buckling strength of a beam and showed that critical buckling strength is influenced by the in-plane temperature variance controlled by the heat source location. Raphael et al 6 showed that the mechanical buckling strength is significantly improved with the slight addition of carbon nanotubes (CNT) in a glass fibre reinforced composite beam.…”
Section: Introductionmentioning
confidence: 99%